Perioperative chemotherapy with or without epidermal growth factor receptor blockade in unselected patients with locally advanced oesophagogastric adenocarcinoma: Randomized phase II study with advanced biomarker program of the German Cancer Society (AIO/CAO STO-0801). (April 2018) - Stahl, Michael; Maderer, Annett; Lordick, Florian; Mihaljevic, Andre L.; Kanzler, Stefan; Hoehler, Thomas; Thuss-Patience, Peter; Mönig, Stefan; Kunzmann, Volker; Schroll, Sebastian; Sandermann, Andreas; Tannapfel, Andrea; et al.
Abstract: Background: Perioperative chemotherapy significantly improves survival in patients with locally advanced oesophagogastric cancer (EGC). However, as approximately 60% of patients will die from their disease, new therapeutic agents such as molecular-targeted drugs are needed. Patients and methods: To evaluate the role of panitumumab with perioperative chemotherapy, previously untreated patients with locally advanced EGC received, in an open-label randomised phase II study (NEOPECX), standard epirubicin, cisplatin, capecitabine (ECX) chemotherapy with or without panitumumab. The primary end-point was the histological response rate after neoadjuvant therapy. The expression status and gene copy number of EGFR, HER2, and MET were determined by immunohistochemistry and fluorescence in situ hybridization (FISH). Plasma samples were collected before the first cycle of neoadjuvant chemotherapy. Results: Overall, 160 patients (80 versus 80) were eligible. The majority (82% versus 80%) showed lymph node involvement. Rate of R0-resection, percentage of patients with downstaging to ypT0-2 at pathohistological evaluation, and rate of major histological response was equal in both arms. Toxicity was increased by panitumumab with regard to thromboembolic events and skin toxicity. Patients with tumour EGFR, HER2 or MET expression had shorter progression-free and overall survival. FISH positivity for these markers was associated with shorter survival independent of therapy. High levels of soluble EGFR in particular predicted poor survival in the panitumumab arm. Conclusion: The addition of panitumumab to ECX did not improve downstaging of locally advanced EGC. Low plasma levels of pathway-associated proteins such as sEGFR may identify a group of patients that benefit from EGFR-directed therapy. ClinicalTrials.gov: NCT01234324 . Highlights: Perioperative CTX with epidermal growth factor receptor (EGFR) blockade did not improve downstaging of tumours. EGFR, HER2 or MET expression and fluorescence in situ hybridization positivity is associated with shorter progression-free survival and overall survival. Soluble EGFR (plasma) may identify a subgroup of patients that definitely will not benefit from EGFR-directed therapy. EGFR targeting plus CTX is not valuable in unselected advanced gastric cancer.